PEMBAGIAN HARTA BERSAMA KARENA PERCERAIAN BAGI MASYARAKAT ADAT BATAK TOBA (Studi Kasus Terhadap Putusan-Putusan di Pengadilan Negeri Pematangsiantar Antara Tahun 2011-2016) - Cristina Natalia Tarigan; Rosnidar Sembiring; Utary Maharany Barus; Idha Aprilyana Sembiring (Universitas Sumatera Utara, 2018)
ABSTRACT Marriage under Article 1 of Law No. 1 of 1974 concerning Marriage of the inner birth bond between a man and a woman as husband and wife in order to form a happy and eternal family or household based on the One Supreme Godhead. One of the causes of marriage breakup is due to divorce. Divorce is the breaking up of a legal marriage before a court Judge. The consequences of the breaking of marriage will cause various problems that is against the child, the status of husband and wife, and to marital property. Article 37 of Law No. 1 of 1974 concerning Marriage when marriage is terminated due to a divorce, joint property is regulated according to their respective laws (religious law, customary law and court rulings). Speaking of marriage, divorce, sharing of common property and death is inseparable from the religious rules and customary rules for indigenous Batak Toba people. The classification of the distribution of common property in Batak Toba community registered in Pematangsiantar District Court Year 2011-2016 there are two decisions. The formulation of the problem in the thesis research is how the division of joint property due to divorce under the Act No.1 of 1974 on Marriage and based on customary law of Batak Toba. How is the application of Law No.1 of 1974 about Marriage to Toba Batak custom law related with division of joint property because divorce. What is the legal judgment made by the Judge of the decisions on the distribution of joint property due to a divorce in the Pematangsiantar District Court. The type of research in preparing the thesis is an empirical or sociological juridical research method. The nature of the thesis research is descriptive analytical. The results of the study when using the Law No. 1 of 1974 on Marriage regulate in Article 37 stating that if marriage is terminated due to divorce, property is regulated according to their respective laws (religious law, customary law, court decision). The division of joint property is then valued in amounts to be divided in half to the parties, referring to Article 128 of the Civil Code. The establishment of Law No. 1 of 1974 on Marriage gives effect based on the application of Marriage Law which is based on husband and wife position in marriage with shared shared property. The basis of judges' consideration is based on Articles 35, 36 and 37 of Law No. 1 of 1974 concerning Marriage of joint property shall act in agreement of both parties. Suggested in the distribution of common property for indigenous Toba Batak people in case of prior dispute with non litigation or custom lane. If it can not resolve it customarily then it can pass through litigation lane in State Pengadlilan in order to obtain equal distribution. Keywords: Marriage, Divorce, Division of Joint Property, Judge's Decision, Customary Law of Batak Toba.